\(\left(1+i\right)^{1000}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 3 2016

\(1+i=\sqrt{2}\left(\cos\frac{\pi}{4}+i\sin\frac{\pi}{4}\right)\)

\(\left(1+i\right)^{1000}=\sqrt{2}^{1000}\left(\cos1000\frac{\pi}{4}+i\sin1000\frac{\pi}{4}\right)\)

                  \(=2^{500}\left(\cos250\pi+i\sin250\pi\right)=2^{500}\)

1 tháng 4 2017

a) (3 + 2i)[(2 – i) + (3 – 2i)]

= (3 + 2i)(5 – 3i) = 21 + i

b)(4−3i)+1+i2+i=(4−3i)+(1+i)(2−i)5=(4−3i)(35+15i)=(4+35)−(3−15)i=235−145i(4−3i)+1+i2+i=(4−3i)+(1+i)(2−i)5=(4−3i)(35+15i)=(4+35)−(3−15)i=235−145i

c) (1 + i)2 – (1 - i)2 = 2i – (-2i) = 4i

d) 3+i2+i−4−3i2−i=(3+i)(2−i)5−(4−3i)(2+i)5=7−i5−11−2i5=−45+15i



1 tháng 4 2017

a) 2i(3 + i)(2 + 4i) = 2i(2 + 14i) = -28 + 4i

b)

c) 3 + 2i + (6 + i)(5 + i) = 3 + 2i + 29 + 11i = 32 + 13i

d) 4 - 3i + = 4 - 3i + = 4 - 3i +

= (4 + ) - (3 + )i =



20 tháng 6 2017

\(\left(1+i\right)^{2006}=\left(\left(1+i\right)^2\right)^{1008}=\left(2i\right)^{1008}=2\)

20 tháng 6 2017

câu dưới tuong tu

10 tháng 1 2017

\(\left(z^2+1+3z-2\right)^2+\left(2z-3\right)^2=0\\ \Leftrightarrow\left(z^2+1\right)^2+2\left(z^2+1\right)\left(3z-2\right)+\left(3z-2\right)^2+\left(2z-3\right)^2=0\\ \Leftrightarrow\left(z^2+1\right)^2+2\left(z^2+1\right)\left(3z-2\right)+\left[\left(3z-2\right)^2+\left(2z-3\right)^2\right]=0\\\Leftrightarrow\left(z^2+1\right)^2+2\left(z^2+1\right)\left(3z-2\right)+13\left(z^2+1\right)=0\Leftrightarrow\left(z^2+1\right)\left(z^2+6z+10\right)=0\)

Giải ra được:

\(\left[\begin{matrix}z=\pm i\\z=-3+i\\z=-3-i\end{matrix}\right.\)

3 tháng 9 2018

a) ta có : \(\left(2+i\sqrt{3}\right)^2=2^2+2.2.i\sqrt{3}+\left(i\sqrt{3}\right)^2\)

\(=4+4\sqrt{3}i-3=1+4\sqrt{3}i\)

b) ta có : \(\left(1+2i\right)^3=1^3+3.1^2.2i+3.1.\left(2i\right)^2+\left(2i\right)^3\)

\(=1+6i-6-8i=-5-2i\)

c) \(\left(3-i\sqrt{2}\right)^3=3^3-3.3^2.i\sqrt{2}+3.3.\left(i\sqrt{2}\right)^2+\left(i\sqrt{2}\right)^3\)

\(=27-27\sqrt{2}i-18-2\sqrt{2}i=9-29\sqrt{2}i\)

d) \(\left(2-i\right)^3=2^3-2.2^2.i+2.2.i^2-i^3\)

\(=8-8i-4+i=4-7i\)

1 tháng 4 2017

a) (3 - 2i)(2 - 3i) = (6 - 6) + (-9 -4)i = -13i;

b) (-1 + i)(3 + 7i) = (-3 - 7) + (-7 + 3)i = -10 -4i;

c) 5(4 + 3i) = 20 + 15i;

d) (-2 - 5i).4i = -8i - 20i2 = -8i -20(-1) = 20 - 8i